A critical review of bank stability measures in selected countries with dual banking system - Abdul Karim, Norzitah; Syed Jaafar Alhabshi, Syed Musa; Kassim, Salina; Haron, Razali (Revista Publicando, 2019)
Financial stability is important to the economy to ensure economy growth as well the sustainability of the financial system itself. One of the critical components of financial stability is the stability in the banking sectors, particularly for countries with dual banking system. The banking system is the most develop sectors in the financial sectors and thus the critical components of financial system for countries with dual banking system. Thus, there is an urgent need for a review of the current measures of bank stability. This paper aims to critically review the measures of bank stability in the selected countries with dual banking systems. This review includes the commonly used definition of bank stability, indicators used as a measure of bank stability. The review of bank stability measures is divided into principle-based measures and theoretical based measures. This review contributes to the literature by offering more details analysis on the determinants of bank stability, particularly in the countries with dual banking systems.